2005
DOI: 10.1063/1.2126117
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence spectroscopy of bandgap reduction in dilute InNAs alloys

Abstract: Photoluminescence ͑PL͒ has been observed from dilute InN x As 1−x epilayers grown by molecular-beam epitaxy. The PL spectra unambiguously show band gap reduction with increasing N content. The variation of the PL spectra with temperature is indicative of carrier detrapping from localized to extended states as the temperature is increased. The redshift of the free exciton PL peak with increasing N content and temperature is reproduced by the band anticrossing model, implemented via a ͑5 ϫ 5͒ k·p Hamiltonian.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 19 publications
(31 reference statements)
4
38
1
Order By: Relevance
“…1 This phenomenon has been widely exploited to extend the wavelength of the arsenides into the 1.3 -1.55 μm region for optical communication technologies with the addition of In allowing GaInNAs epilayers to be lattice matched to GaAs or InP substrates. 2 In addition to this, the incorporation of N into narrow gap semiconductors, such as InAs, 3 GaSb 4, 5 and InSb, 6 has been investigated to produce materials for accessing the 2 -5 μm and 8 -14 μm wavelength regions where there are atmospheric transmission windows. In particular, GaNSb alloys, the subject of this Letter, offer the prospect of extending the wavelength of the GaSb band gap from 1.7 μm into the 2-5 μm range, not only to exploit that atmospheric transmission window, but also for thermophotovoltaics and for light emitting diodes for detection of several important gases, such as CH 4 , CO 2 , and CO.…”
Section: Copyright 2011 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…1 This phenomenon has been widely exploited to extend the wavelength of the arsenides into the 1.3 -1.55 μm region for optical communication technologies with the addition of In allowing GaInNAs epilayers to be lattice matched to GaAs or InP substrates. 2 In addition to this, the incorporation of N into narrow gap semiconductors, such as InAs, 3 GaSb 4, 5 and InSb, 6 has been investigated to produce materials for accessing the 2 -5 μm and 8 -14 μm wavelength regions where there are atmospheric transmission windows. In particular, GaNSb alloys, the subject of this Letter, offer the prospect of extending the wavelength of the GaSb band gap from 1.7 μm into the 2-5 μm range, not only to exploit that atmospheric transmission window, but also for thermophotovoltaics and for light emitting diodes for detection of several important gases, such as CH 4 , CO 2 , and CO.…”
Section: Copyright 2011 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…By substituting the group V-atom with low concentrations of nitrogen, large band gap reductions corresponding to wavelengths in the long or very long-wavelength infrared ranges have been reported. [1][2][3][4][5][6][7][8][9][10][11][12] The strong modification of the conduction band when dilute amounts of the host anion of the compound semiconductor is replaced is thought to be caused by N-induced states lying near to the conduction band minimum. [13][14][15][16][17][18][19][20][21] For the alloy GaN x Sb 1Àx , the band gap red shift is especially large.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the BAC parameters for InAsN are usually determined with low accuracy. Recently, Zhuang et al 12 performed PL studies on InAsN/InAs samples similar to those studied in this work, and obtained a value of C MN = 2.5 eV at 4 K and a value of C MN = 2.7 eV at 300 K. Kudrawiec et al 18 reported PR spectra of similar samples with N contents up to ϳ1% and obtained C MN = 2.7 eV at 20 K. Previous studies obtained much lower C MN values ͑Veal et al 11 found a value of C MN = 1.77 eV with PL at 80 K; Shih et al 9 and Kuroda et al 6 performed absorption measurements at 300 K and obtained C MN = 1.68 eV and 1.86 eV, respectively, after correcting for the Burstein-Moss effect͒. Vurgaftman and Meyer 31 give a recommended value of 2.0 eV.…”
Section: Pl and Optical Absorptionmentioning
confidence: 78%
“…5,9,[11][12][13]18 The results are usually analyzed in terms of the BAC model, which allows one to calculate the fundamental band gap energy of InAs 1−x N x ͑i.e., the energy of the E − subband͒ as a function of composition…”
Section: Pl and Optical Absorptionmentioning
confidence: 99%